Utilization of Digital Information Systems in Improving the Quality of Al-Qur’an Memorization (Case Study of Grade 1 Students of Al-Amien Prenduan Sumenep Middle School of Al-Qur’an Memorization 2026) - Haidar Rifqi Ghassany; Ghozi Mubarok (al-Afkar, Journal For Islamic Studies, 2026)
This research was conducted to examine the use of digital information systems to improve the quality of Quran memorization in junior high school students. The background of this research is based on the demands of Quran memorization educational institutions to adapt digital technology as a supporting instrument for learning and monitoring Quran memorization. The purpose of this study is to analyze the concept of digital information systems, describe their implementation by Quran memorization administrators and student guardians, and identify supporting and inhibiting factors in improving the quality of Quran memorization in first-grade junior high school students. This research used a qualitative approach with a case study approach. Data collection techniques included in-depth interviews, observation, and documentation. Data analysis was conducted interactively through data reduction, data presentation, and drawing conclusions using triangulation techniques to ensure data validity. The results indicate that digital information systems play a role in increasing transparency, the effectiveness of memorization monitoring, and the involvement of student guardians. However, optimizing their use still faces obstacles such as limited digital literacy, technology access, and system stability. This study confirms that the integration of digital information systems with tahfizh learning management and Islamic boarding school culture is able to improve the quality of tahfizh Al-Qur’an in a sustainable manner.